Analysis of consumer attitudes to purchase intentions of counterfeiting bag product in Indonesia - Santi Budiman (International Journal of Management, Economics and Social Sciences (IJMESS), 2012)
Fashion handbags are products that occupy the third position of the 11 types of products most often hijacked. According to the United States Customs and Border Protection and European Commission, Indonesia is a country that ranked the 8th largest country after Hong Kong with the highest levels of product piracy in Asia in 2006. This study investigate the effect of product cues factors, including extrinsic cues and intrinsic cues, Attitudes towards counterfeits, religiosity, lawfulness attitudes, status of consumption on purchase intentions. This study aims to explain the process of forming an intention to buy pirated bag products that rest on the primary relationship of independent variables like attitudes towards counterfeit, lawfulness attitudes and consumption status of the intention to buy pirated products as well as test patterns bag relationship between variables. The data was collected by using a questionnaire enclosed with the statement that based on the Likert scale. The respondents were all employed women who are in the area of Yogyakarta with 200 respondents. These results show that intrinsic factors had positive influence on consumer attitudes towards pirated handbags addition, a more positive attitude of consumers towards pirated bags will further strengthen the purchasing intentions and conversely the higher the status of a consumer's consumption will only further weaken the intention of purchasing the product bag pirated.
Keywords: 330; extrinsic cues; intrinsic cues; attitudes towards counterfeits; religiosity; lawfulness attitudes; status of consumption; purchase intention